Finding the Form of God in Philippians 2: Gregory of Nyssa and the Development of Pro-Nicene Exegesis - Weedman, Mark (Journal of theological interpretation, 2008)
I argue that Gregory of Nyssa reshaped the Logos-Sarx theological motif through his use of a new theological exegesis of the Christ Hymn in Phil 2. In his argument against Apollinarius, Gregory draws on an earlier Pro-Nicene exegetical tradition, one that was originally formulated in the 350s against the anti-Nicene Homoians by theologians such as Hilary of Poitiers. This exegetical tradition centered on Phil 2:6-7, and it was intended to demonstrate the unity of the Son's divinity and humanity against Homoian attempts to use the distinction between divinity and humanity in the Son to subordinate the Son to the Father. In this reading, Gregory's problem with Apollinarius is that Apollinarius's theology violates something central to the Pro-Nicene tradition that Gregory had inherited, namely, the need to preserve the union of the full divinity and humanity in the Son. Without this, Gregory believes, key aspects of Pro-Nicene faith and practice, especially its account of divinization, fall apart. By using Phil 2 to construct a new theological motif, Gregory can articulate a Christology that has deep exegetical roots and overcomes the limitations of the Logos-Sarx model.